A new combined therapy for functional organ preservation and survival in lateral oropharyngeal wall cancer. (August 2014) - Furusaka, Tohru; Matsuda, Akira; Tanaka, Akane; Matsuda, Hiroshi; Asakawa, Takeshi; Shigihara, Shuntaro
Abstract Conclusion: The outcome of this treatment was good, indicating that it is safe and effective. A favorable outcome was obtained, especially in patients with T3, N0–1, and N2a–b cancer, while outcome remained unfavorable in patients with T4a and N2c cancer. Consideration should be given to the need for intensity-modulated radiation therapy (IMRT) and maintenance therapy. Objective: To improve the survival and functional organ preservation rates in patients with lateral oropharyngeal squamous cell carcinoma. Methods: The primary site was treated conservatively by neoadjuvant chemotherapy and/or concurrent chemoradiation therapy. Chemotherapy was administered by superselective intra-arterial infusion and cervical lymph node metastasis was treated by radical neck dissection. Results: Among 71 patients, the 5- and 10-year overall survival rates were 85.1% and 63.5%, respectively; and the 5- and 10-year functional organ preservation rates were 61.0% and 51.6%, respectively. The outcomes were especially good in patients with T3 N0–1, and N2a–b cancer. All patients with N2c cancer had poor outcomes.